PENGARUH MODEL PEMBELAJARAN SAVI BERBANTUAN MEDIA LITERACY CLOUD TERHADAP KETERAMPILAN MENYIMAK TEKS NARASI SISWA SEKOLAH DASAR - Widia Triyana; Indah Nurmahanani; Dede Wahyudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research has several objectives, namely: 1) to determine the improvement in narrative text listening skills of students who receive learning using the SAVI model assisted by media literacy cloud and students who receive learning using the problem based learning model; 2) determine the effect of implementing the SAVI learning model assisted by media literacy cloud on students' narrative text listening skills. The method used is an experiment with a quasi-experimental design in the form of a nonequivalent control group. The research sample was students in class III A and class III B in one of the elementary schools in Subang Regency with a total of 20 students in each class. Data before and after learning was obtained through student listening skills test instruments. The research obtained results that the SAVI model assisted by media literacy cloud improved students' narrative text listening skills as evidenced by the results of the n-gain test which obtained an average of 0.5898 in the medium category. The influence of the SAVI model assisted by media literacy cloud on narrative text listening skills is shown by the results of the t test which gets a significance value of <0.05, so H0 is accepted so that a significant difference is obtained.